PERANCANGAN FILM EDUKASI TAHALANG SUMPAH: FENOMENA LARANGAN PERNIKAHAN ANTARA MASYARAKAT SANIANGBAKA DENGAN SINGKARAK - MUHAMMAD FADJRIN HERMANA PUTRA, Drs. Syafwan, M.Si., San Ahdi, S.Sn., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Indonesia has many tribes, one of them is Minangkabau. Minangkabau has many unique folklore that could be an education material for the people in this modern era, in example the story from Saniangbaka and Singkarak. The objective of the Tahalang Sumpah movie is to give information an educate about prohibited marriage between people from Saniangbaka with Singkarak.Descriptive qualitative method is used in this movie making process. The data are collected from interviews, observations, field notes, and documentations. This movie are made with theory of visual communication design, audio visual, cinematography, and layout. 5W=1H analysis is also used in the process.Supporting media such as movie trailer, Instagram account, original soudtrack, poster, x-banner, sticker, and movie screening inviation is created to support the movie exixtence.Keyword : Educational movie, prohibited marriage